(untitled) (Applied Biological Research, 2018)
Ten agro-industrial co-products (AICP) viz., wheat (WB) and deoiled rice (DORB), gram chuni of green gram (GGC) and hyacinth bean (HBC), husk of Bengal gram (BGH), pigeon pea (PPH), hyacinth bean (HBH) and soy (SH) and ground shells of groundnuts (GSL) and almond (ASL) were evaluated for chemical composition and fermentation value (FV) aiding in the selection of feedstuffs in dairy rations. Total carbohydrates in AICPs consisted of 55 to 80% of NDF and 20 to 25% of NFC. CP in DORB was 49% bound to ADF but in other AICPs it was < 2.5%. Although macronutrient composition of DORB was better than WB, FV of DORB was 50% lesser than WB. Among husk, IVGP was higher in the order of HBH> SH> PPH> BGH which was more related to hemicellulose content than other cell wall constituents. Although fermentation rate of GSL and ASL were above 10% like WB, their extent of fermentation was 75 to 85% lesser than WB. Brans fermentation was ≥10% h-1 while gram chuni were fermented at a rate of 5 to 9% h-1. Husk fermentation rate was slow (3 to 6% h-1). CO2 to methane ratio, extent and rate of fermentation were critical kinetic attributes to differentiate FV of AICPs. Net gas production of AICPs was greater with higher hemicellulose. Studies conclude that NGP or hemicelluloses of brans, chunis, husks or shells could be criteria for their selection to incorporate in dairy cattle ration.